Zika Virus Infection in Pregnant Women and Microcephaly - Duarte, Geraldo; Moron, Antonio Fernandes; Timerman, Artur; Fernandes, César Eduardo; Mariani Neto, Corintio; Almeida Filho, Gutemberg Leão de; Werner Junior, Heron; Espírito Santo, Hilka Flavia Barra do; Steibel, João Alfredo Piffero; Bortoletti Filho, João; Andrade, Juvenal Barreto Borriello de; Burlá, Marcelo; Silva de Sá, Marcos Felipe; Busso, Newton Eduardo; Giraldo, Paulo César; Moreira de Sá, Renato Augusto; Passini Junior, Renato; Mattar, Rosiane; Francisco, Rossana Pulcineli Vieira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
From the discovery of the Zika virus (ZIKV) in 1947 in Uganda (Africa), until its arrival in South America, it was not known that it would affect human reproductive life so severely. Today, damage to the central nervous system is known to be multiple, and microcephaly is considered the tip of the iceberg. Microcephaly actually represents the epilogue of this infection's devastating process on the central nervous system of embryos and fetuses. As a result of central nervous system aggression by the ZIKV, this infection brings the possibility of arthrogryposis, dysphagia, deafness and visual impairment. All of these changes of varying severity directly or indirectly compromise the future life of these children, and are already considered a congenital syndrome linked to the ZIKV. Diagnosis is one of the main difficulties in the approach of this infection. Considering the clinical part, it has manifestations common to infections by the dengue virus and the chikungunya fever, varying only in subjective intensities. The most frequent clinical variables are rash, febrile state, non-purulent conjunctivitis and arthralgia, among others. In terms of laboratory resources, there are also limitations to the subsidiary diagnosis. Molecular biology tests are based on polymerase chain reaction (PCR) with reverse transcriptase (RT) action, since the ZIKV is a ribonucleic acid (RNA) virus. The RT-PCR shows serum or plasma positivity for a short period of time, no more than five days after the onset of the signs and symptoms. The ZIKV urine test is positive for a longer period, up to 14 days. There are still no reliable techniques for the serological diagnosis of this infection. If there are no complications (meningoencephalitis or Guillain-Barré syndrome), further examination is unnecessary to assess systemic impairment. However, evidence is needed to rule out other infections that also cause rashes, such as dengue, chikungunya, syphilis, toxoplasmosis, cytomegalovirus, rubella, and herpes. There is no specific antiviral therapy against ZIKV, and the therapeutic approach to infected pregnant women is limited to the use of antipyretics and analgesics. Anti-inflammatory drugs should be avoided until the diagnosis of dengue is discarded. There is no need to modify the schedule of prenatal visits for pregnant women infected by ZIKV, but it is necessary to guarantee three ultrasound examinations during pregnancy for low-risk pregnancies, and monthly for pregnant women with confirmed ZIKV infection. Vaginal delivery and natural breastfeeding are advised.
Keywords: pregnancy complications; Zika virus; arbovirus infections; microcephaly/ultrasonography; real-time polymerase chain reaction; deafness/ etiology; blindness/ etiology